Pengaruh Kepemimpinan Kepala Sekolah, Lingkungan Kerja dan Employee Engagement terhadap Kinerja Guru SMA XYZ Palembang - Juniarti Manalu (Departement of Mathematics Education, 2023)
The achievement of the vision and mission of an educational institution is strongly influenced by the teacher. As educators, teachers have a crucial role for the sustainability of a school as an education institution. Teachers' performance is used as a measure of the quality of the teaching and learning process. This study aims to examine the influence of the principal's leadership, work environment and employee engagement on teacher performance at SMA XYZ Palembang. This study used quantitative methods with 28 teachers as respondents. The technique of data collection is by using a questionnaire. The data analysis method used is descriptive analysis and statistics analysis using SmartPLS Software with Structural Equation Modeling (SEM). The result showed that the principal’s leadership factor, work environment and employee engagement had an effect on increasing teacher performance by 36.2% and the principal’s leadership factor and work environment had an effect on increasing employee engagement by 37.2%.